Study on pulsed DC-sputtering of iridium oxide for implantable electrodes - Dias, N. S. (2007)
A pulsed-DC reactive sputtering technique was used for iridium oxide thin-film deposition. Frequency, pulse width, oxygen flow and deposition time were changed over several deposition sessions, regarding implantable electrode applications. Surface and electrochemistry analysis were performed for deposition evaluation. The results evidenced that the deposited film sputtered with 2 sccm of oxygen flow and 50 KHz pulse frequency, achieved best surface structure and electrochemical properties. Impedance tests revealed an almost purely resistive behaviour for stimulation signal frequencies 0.1-10 KHz, with a value of 150 Ω